MALE GAZE IN THE DJARUM 76 CIGARETTE ADVERTISEMENT (VERSION OF MINTA APA...???) - Yuniar, Puput (Sintesa, 2024)
Advertisements often prioritize commercial interests by presenting women as objects because they are an element that can make a profit. Ramadhan's research (2020) shows that Male Gaze is an approach that can be done for cigarette advertisements because the target audience of cigarette advertisements is generally adults who are smokers and are dominantly male. The advertisements aired on DJARUM 76 cigarettes are adult activities as shown by a handsome male figure with an athletic body that is the concern of many women, in addition to reinforcing roles that relate to strength, risk taking, and dominance. The phenomenon of objectification of women should be examined, considering that cigarette advertisements and women do not have a direct link, so researchers assume that the DJARUM 76 advertisement version "Minta Apa ...???" is intended to entertain among men only. because advertising on DJARUM 76 has considerable power in shaping social perceptions and cultural norms and its influence on society. This research is descriptive qualitative with Gillian Rose's visual analysis method: Site of production, site of image itself, and site of audiencing. This objective is to describe how the Male Gaze is represented in DJARUM 76 cigarette advertisement (version MINTA APA...???). Overall, this advertisement represents Male Gaze elements in each scene and how the male-dominated audience interprets the visual objects they see in this advertisement as erotic objects that are able to cause sexual desire in men. Theoretical recommendations are expected that future research with similar topics use Standpoint theory in analyzing Male Gaze. Practical recommendations are expected that similar research objects with a research focus on the impact of Male Gaze on women, gender stereotypes, audience perceptions, and gender discrimination in the media. Keywords: Cigarette Advertisement, Male Gaze, Visual Analysis, Djarum 76, Media